The Outcome of Cochlear Implantations in Deaf-Blind Patients: A Multicenter Observational Study. Issue 8 (September 2022) - Daneshi, Ahmad; Sajjadi, Hamed; Blevins, Nikolas; Jenkins, Herman A.; Farhadi, Mohammad; Ajallouyan, Mohammad; Hashemi, Seyed Basir; Thai, Anthony; Tran, Emma; Rajati, Mohsen; Asghari, Alimohamad; Mohseni, Mohammad; et al.
Abstract : Objective: This multicenter study aimed to evaluate the auditory and speech outcomes of cochlear implantation (CI) in deaf-blind patients compared with deaf-only patients. Study Design: Retrospective cohort study. Setting: Multiple cochlear implant centers. Patients: The current study was conducted on 17 prelingual deaf-blind children and 12 postlingual deaf-blind adults who underwent CI surgery. As a control group, 17 prelingual deaf children and 12 postlingual deaf adults were selected. Intervention: Cochlear implantation. Main Outcome Measure(s): Auditory and linguistic performances in children were assessed using the categories of auditory performance (CAP) and Speech Intelligibility Rating (SIR) scales, respectively. The word recognition score (WRS) was also used to measure speech perception ability in adults. The mean CAP, SIR, and WRS cores were compared between the deaf-only and deaf-blind groups before CI surgery and at "12 months" and "24 months" after device activation. Cohen's d was used for effect size estimation. Results: We found no significant differences in the mean CAP and SIR scores between the deaf-blind and deaf-only children before the CI surgery. For both groups, SIR and CAP scores improved with increasing time after the device activation. The mean CAP scores in the deaf-only children were either equivalent or slightly higher than those of the deaf-blind children at "12 months post-CI" (3.94 ± 0.74 vs 3.24 ± 1.25; mean difference score, 0.706) and "24 months post-CI" (6.01 ± 0.79 vs 5.47 ± 1.06; mean difference score, 0.529) time intervals, but these differences were not statistically significant. The SIR scores in deaf-only implanted children were, on average, 0.870 scores greater than the deaf-blind children at "12 months post-CI" (2.94 ± 0.55 vs 2.07 ± 1.4; p = 0.01, d = 0.97) and, on average, 1.067 scores greater than deaf-blind children at "24 months post-CI" (4.35 ± 0.49 vs 3.29 ± 1.20; p = 0.002; d = 1.15) time intervals. We also found an improvement in WRS scores from the "preimplantation" to the "12-month post-CI" and "24-month post-CI" time intervals in both groups. Pairwise comparisons indicated that the mean WRS in the deaf-only adults was, on average, 10.61% better than deaf-blind implanted adults at "12 months post-CI" (62.33 ± 9.09% vs 51.71 ± 10.73%, p = 0.034, d = 1.06) and, on average, 15.81% better than deaf-blind adults at "24-months post-CI" (72.67 ± 8.66% vs 56.8 ± 9.78%, p = 0.002, d = 1.61) follow-ups. Conclusion: Cochlear implantation is a beneficial method for the rehabilitation of deaf-blind patients. Both deaf-blind and deaf-only implanted children revealed similar auditory performances. However, speech perception ability in deaf-blind patients was slightly lower than the deaf-only patients in both children and adults.